Implementasi Tugas dan Tanggung Jawab Kanit Reskrim Dalam Meningkatkan Kinerja Anggota Reskrim Pada Polsek Karawang Kota - Meyke Kurniawati; Uus MD Fadli (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This research is to find out to what extent the Duties and Responsibilities of the Criminal Investigation Unit in Improving the Performance of Criminal Investigations at the Karawang City Police. This study uses an observative approach. The population in this study is to solve the problem of the ability of the personnel themselves, it is still found that investigators do not yet have SKACP certificates (investigator competency certificates). Observative method by proving into place directly. The results of this study indicate that there is a lack of ability of Criminal Investigation personnel in investigations, so training must be given so that their work results are maximized. The results show that many agree that holding training for investigators in members of the Criminal Investigation Unit has a positive influence on the duties and responsibilities of the Criminal Investigation Unit.